Daytime shooting star. 10 - Yamamori, Mika (Shojo beat manga., 2021)
"Suzume has moved to Tokyo and is living with her uncle. Mamura's sudden confession of love leaves Suzume's head spinning. After spending the entire night agonizing over how to respond to him, she finally decides to give Mamura a chance. But soon after she makes her choice, Mr. Shishio throws her a curveball!"--Provided by publisher.